2002
DOI: 10.1128/jb.184.20.5814-5817.2002
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of α-Amylase from Pseudoalteromonas haloplanktis TAB23: Two Different Pathways in Different Hosts

Abstract: Secretion of cold-adapted ␣-amylase from Pseudoalteromonas haloplanktis TAB23 was studied in three Antarctic bacteria. We demonstrated that the enzyme is specifically secreted in the psychrophilic hosts even in the absence of a protein domain that has been previously reported to be necessary for ␣-amylase secretion in Escherichia coli. The occurrence of two different secretion pathways in different hosts is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
(21 reference statements)
4
30
0
Order By: Relevance
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 80%
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 80%
“…This also gives evidence of the versatility of the culturable microbiota from Potter Cove to take advantage of the nutrient sources, which are sometimes scarce in the Antarctic. In fact, Pseudoalteromonas isolates showed a great potential for the bioprospection of a great number of enzymes, in accor− dance with other reports (Holmström and Kjelleberg 1999;Truong et al 2001;Tutino et al 2002;Van Petegem et al 2003;Zeng et al 2006). The versatile hydrolytic capacity exhibited by this genus and its remarkable abundance among the producers of cold enzymes suggest its relevance to the recycling of organic matter.…”
Section: Discussionsupporting
confidence: 73%
“…The development of genetic tools for manipulation of Antarctica bacteria (Parrilli et al, 2008a) allowed us to demonstrate that the C-terminal propeptide is not mandatory for a-amylase recombinant secretion either in the source strain or in the related strain P. haloplanktis TAC125 (Tutino et al, 2002). Indeed, the propeptide can be replaced by other protein domains without affecting the secretion of the chimeric proteins (Cusano et al, 2006b;Parrilli et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Although the C-terminal propeptide sequence is not homologous to that of b-autotransporters (Henderson et al, 2004), in a previous paper (Feller et al, 1998) it was suggested that it may function as a protein secretion helper when amylase is produced in Escherichia coli. However, different results were obtained when the secretion of recombinant a-amylase and its truncated version, devoid of the C-terminal domain, was investigated either in the enzyme source strain, P. haloplanktis TAB23, or in another Antarctic bacterium, P. haloplanktis TAC125 (Tutino et al, 2002). It was demonstrated that the Cterminal propeptide is not mandatory for a-amylase secretion and that the presence of the C-terminal domain does not interfere either with the secretion kinetics or with the maximal secretion and production yield (Tutino et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation